METHOD AND EPISTEMOLOGY IN MARX’S THEORY OF STATE AND ECONOMY IN THE GRUNDRISSE: REDUCIONISM, SYSTEMS AND COMPLEXITY - Folloni, André (European Scientific Journal, ESJ, 2014)
This article aims to show Marx’s methodology thought as it is exposed in his Grundrisse der Kritik der politischen Ökonomie, ordinarily referred as Grundrisse. This methodology lies behind his theories of economy and State. The paper examines only the parts of the Grundrisse where Marx explicitly writes about methodology and describes how his intellectual way is walked. These objective of the paper is to compare Marx’s methodology conceptions to the contemporary issues of the systems and complexity epistemology. By doing that, the article perceives that in some aspects Marx’s epistemology is ahead of its time, working with some conceptions that would be later developed by the 20th and 21st centuries epistemology. In other aspects, however, Marx appears as a product of his time, and some other conceptions present in his works are now overcame by the development of methodology and epistemology thoughts.